2019
DOI: 10.14260/jemds/2019/802
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Prevalence and Association of Dry Eye Disease with Visual Display Terminal Use in Children- A Cross Sectional Observational Study

Abstract: BACKGROUND Paediatric dry eye disease is a major health concern. VDT's like laptops, tablets and smart phones are very commonly in use in children. Our study was done to evaluate percentage of DED in children and to evaluate association between VDT use and DED in children. METHODS A cross sectional study was conducted in ophthalmology OPD of a tertiary eye care centre for a duration of one year. All children between 6-16 years of age were included. Exclusion criteria included any ocular surgery in past 6 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Investigations of ocular surface effects of smartphone use in children have focussed on children with dry eye. Studies in school-aged children with dry eye found increased dry eye symptoms with self-reported smartphone use of more than one [ 27 ] and 3 h [ 29 ] per day, relative to control with healthy eyes. Similarly, studies conducted in school-aged children with dry eye showed a reduction in ocular symptoms following cessation of smartphone use for one month [ 17 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of ocular surface effects of smartphone use in children have focussed on children with dry eye. Studies in school-aged children with dry eye found increased dry eye symptoms with self-reported smartphone use of more than one [ 27 ] and 3 h [ 29 ] per day, relative to control with healthy eyes. Similarly, studies conducted in school-aged children with dry eye showed a reduction in ocular symptoms following cessation of smartphone use for one month [ 17 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…[22], [23], [24] In this study, the division of play duration used was < 2 hours, 2-4 hours and > 4 hours. [9], [16], [17] Data on the degree of dry eye complaints and quality of life of samples in this study were taken using the DEQS questionnaire with a dry eye degree score consisting of the lowest value of 0, which showed no indication of dry eyes and the highest score of 100 indicating severe symptoms. Quality of life data was taken based on the sample's subjective answers to the last question from the DEQS questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Research by Lee et al [9] reported the use of VDT for non-stop gaming for four hours a day is more at risk of experiencing CVS whose one component is dry eye. Research conducted by Sodani et al [17] reported the use of VDT at night with a duration of > one hour for gaming increases the risk of getting dry eye symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by a disruption in the tear film, resulting in the drying of tears. This condition is commonly associated with decreased intervals between blinking [10,11]. Continuous use of screens can cause eye fatigue and soreness, which contributes to the eye injury and diseases like refractive error, myopia, cataract, and glaucoma [12].…”
Section: Introductionmentioning
confidence: 99%